Preface - Kátai, János (Acta Agraria Debreceniensis, 2010)
In the frame of a common “Hungarian-Ukrainian Intergovernmental S&T Cooperation Programme” which title is “Change of soils ecological characteristics of Ukraine and Hungary in the conditions of anthropogenic transformed ecosystems and optimization of biological processes of plants primary feeds elements mobilization” a Workshop was held in Debrecen. The member institutes of project participated with different presentation in this program. The title of Workshop was: “Anthropogenic effect on the properties of Middle and Eastern European chernozem soils and on the sustainable agricultural production”. The aim of the Workshop was to give relevant information about the present situation of the Middle and Eastern European Chernozem soils, especially emphasize the effect of different loading on the quality (properties) of chernozem soils. With the Workshop we would like to create a tradition for discussion about the anthropogenic effect on the soil properties and through it on the productivity of different soils. It was a forum for discussion of research results related to problems and possibilities for prevention of soil quality. With this possibility we would like to contribute to the sustainable agricultural production. The papers were read for the publisher and we would like to show them in a separate supplement of Journal of Agricultural Sciences, Acta Agraria Debreceniensis as one of the results of the project. The papers comply with the requirements of the scientific issue except those two which show the university and the department of the Ukrainian partner taking part in this project. The participant Institutes of the project: - Dnepropetrovsk National University, Faculty of Biology and Ecology; - Kryvyi Rig Botanical Garden NAS of Ukraine, Plant Physiology & Soil Biology Department; - Department of Agrochemistry and Soil Sciences of Centre for Agricultural and Applied Economics; - Research Institute of Karcag, Centre for Agricultural and Applied Economics. The collaboration with Ukrainian partners was successful and we have confidence in the further cooperation in scientific research.